2020
DOI: 10.28982/josam.729546
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of peripheral vascular injuries treated with surgery: A retrospective cohort study

Abstract: Ethics Committee Approval: Ethics committee approval was not received due to the retrospective nature of the study. All procedures in this study involving human participants were performed in accordance with the 1964 Helsinki Declaration and its later amendments. Etik Kurul Onayı: Çalışmanın retrospektif doğası nedeniyle etik kurul onayı alınmadı. İnsan katılımcıların katıldığı çalışmalardaki tüm prosedürler, 1964 Helsinki Deklarasyonu ve daha sonra yapılan değişiklikler uyarınca gerçekleştirilmiştir.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Penetrating injuries constitute 5 -20% of abdominal injuries due to firearms (17). The most common causes of peripheral vascular injuries have been identified as firearms in the USA, blunt traumas in European countries, and cutting tools in Turkey due to iatrogenic reasons (18). Unlike other studies, the present study revealed that 30.3%, 22.7%, 22.7%, 16.7%, and 7.6% of patients were injured in the abdomen, the head and neck, the thorax, the lower extremity, and the upper extremity, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Penetrating injuries constitute 5 -20% of abdominal injuries due to firearms (17). The most common causes of peripheral vascular injuries have been identified as firearms in the USA, blunt traumas in European countries, and cutting tools in Turkey due to iatrogenic reasons (18). Unlike other studies, the present study revealed that 30.3%, 22.7%, 22.7%, 16.7%, and 7.6% of patients were injured in the abdomen, the head and neck, the thorax, the lower extremity, and the upper extremity, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Urgent intervention is required when arterial damage occurs in the lower extremity, as it can result in limb loss or a lethal injury [11,23]. Dorlac et al [24] found that more than half of the patients who were injured by firearms died from excessive blood loss due to artery damage in the lower extremity.…”
Section: Discussionmentioning
confidence: 99%